2016 IEEE Global Engineering Education Conference (EDUCON) 2016
DOI: 10.1109/educon.2016.7474644
|View full text |Cite
|
Sign up to set email alerts
|

Teacher perceptions of training and intention to use robotics

Abstract: this paper presents an overview of a work in progress research project that investigated cycle 2 in-service teachers' perceptions of the effectiveness of a training offered in the United Arab Emirates on how to use and integrate robotics in teaching. The project also investigated teacher beliefs, attitudes and intention to use robotics in their future teaching. A description of the training offered to cycle 2 teachers is presented. Potential contributions to the context and knowledge as well as future work are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In line with other research; there was a positive correlation between perceived usefulness, perceived ease of use, behavioral intention, and use in human-robot interaction in production systems [48], usefulness and ease of use were predictive of adults" attitudinal acceptance of a domestic robot in their home; ease of use and attitudinal acceptance were predictive of intentional acceptance [24], the teacher beliefs, attitudes and intention to use the software in their future teaching [49], this study found that Lego Mindstorms Ev3 as a learning resource had generated the intention of teachers to use it in their classroom so it had a positive impact on the actual use of teachers.…”
Section: Discussionsupporting
confidence: 84%
“…In line with other research; there was a positive correlation between perceived usefulness, perceived ease of use, behavioral intention, and use in human-robot interaction in production systems [48], usefulness and ease of use were predictive of adults" attitudinal acceptance of a domestic robot in their home; ease of use and attitudinal acceptance were predictive of intentional acceptance [24], the teacher beliefs, attitudes and intention to use the software in their future teaching [49], this study found that Lego Mindstorms Ev3 as a learning resource had generated the intention of teachers to use it in their classroom so it had a positive impact on the actual use of teachers.…”
Section: Discussionsupporting
confidence: 84%
“…This result contradicts the results of Venkatesh et al (2003) and the UTAUT, where the attitude factor is omitted. However, this might be understandable in the context of modern studies, which reveal a positive relationship between the attitudes of teachers and technology use (Avidov-Ungar & Eshet-Alkalai, 2011;Naaz, 2012;Santos et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Zacharia et al ( 2015 ) developed the Simulation Acceptance Model (SAM) to address the need for an instrument for researching teachers' beliefs, attitudes, and intentions to use simulations for educational purposes. Santos et al ( 2016 ) used SAM to assess teachers’ beliefs, attitudes, and intentions to use the Lego Mindstorms software in their teaching. Later, Park and Han ( 2016 ) developed a variation of the Technology Acceptance Model, called the Robot Service Acceptance Model (RSAM), that is specialized in examining teachers’ views on robot-assisted learning environments with a cloud service platform.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Aksu and Durak ( 2019 ) also studied in-service teachers’ views on robotics but in the context of robotic tournaments, while Çiftçi et al ( 2020 ) explored pre-service early-childhood teachers’ views on STEM education and their STEM teaching practices. Prior to these studies, Santos et al ( 2016 ) researched in-service teachers’ beliefs, attitudes, and intention to use robotics in their future teaching, while Khanlari ( 2013 ) explored in-service teachers' perceptions of the effects of robotics on students’ personal skills and abilities. According to these studies, teachers hold positive views of ER and its impact on students’ learning.…”
Section: Introductionmentioning
confidence: 99%